2020
DOI: 10.1038/s41598-019-57152-w
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals bioconcentration in Crassostrea rhizophorae: A site-to-site transplant experiment at the Potengi estuary, Rio Grande do Norte, Brazil

Abstract: in this study, we analyzed the bioconcentration of cd, cr, cu, pb, ni, and Zn in the soft tissue of transplanted oysters in two sites in the potengi estuary for six months. native oysters collected before and after the transplantation experiment provided the background for statistical analyses. cd, cr, and ni showed a strong inverse correlation with oyster weight in both sites. transplantation upstream of the estuary presented increasing concentrations of Zn, cu, and pb and condition index (ci) and decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Thus, we observed that metal concentrations in oysters from CIEC are similar to those observed in animals from other estuaries under anthropogenic influence. Senez-Mello et al (2020) found 0.11mg kg -1 of Cd, 0.08mg kg -1 of Cr, 0.05mg kg -1 of Pb and 294mg kg -1 of Zn in the Potengi estuary (Northeast Brazil). However, concentration of Zn in oysters from CIEC was higher than in other coastal areas of the NE Brazil, such as 309mg kg -1 in the Todos os Santos Bay (Amado-Filho et al, 2008) and 154mg kg -1 in the estuary of Rio dos Cavalos, Rio Grande do Norte (Silva et al, 2003).…”
Section: Metals In the Ciec Biotamentioning
confidence: 96%
“…Thus, we observed that metal concentrations in oysters from CIEC are similar to those observed in animals from other estuaries under anthropogenic influence. Senez-Mello et al (2020) found 0.11mg kg -1 of Cd, 0.08mg kg -1 of Cr, 0.05mg kg -1 of Pb and 294mg kg -1 of Zn in the Potengi estuary (Northeast Brazil). However, concentration of Zn in oysters from CIEC was higher than in other coastal areas of the NE Brazil, such as 309mg kg -1 in the Todos os Santos Bay (Amado-Filho et al, 2008) and 154mg kg -1 in the estuary of Rio dos Cavalos, Rio Grande do Norte (Silva et al, 2003).…”
Section: Metals In the Ciec Biotamentioning
confidence: 96%
“…Indeed, biomonitoring bivalve molluscs for human consumption shows alarming values of Zn and Cd contents, in the low estuary region of the JPE (Silva et al, 2001). Also above the limit allowed for human consumption are Cu contents (Senez-Mello et al, 2020). The contaminants concentration accumulated in a biomonitor denote its bioavailability in the organism, at the place and time of exposure (Silva et al, 2006).…”
Section: Sediment Toxicitymentioning
confidence: 99%
“…The prevalence of low energy and currents from the waves in estuaries makes the pollutants accumulate in sediments instead of dispersing [10]. The types of pollutants found in estuaries are heavy metals [11,12], radionuclides [13], and pathogens such as bacterial pathogens [14], protozoa [15], enteric viruses [16], and fungus [14]. Furthermore, antibiotics, antibiotic resistant genes, and MPs are regarded as important emergent pollutants in the estuarine ecosystem due to their widespread distribution, persistence, and impact on the environment and human health [17].…”
Section: Introductionmentioning
confidence: 99%